2020
DOI: 10.1016/j.eurpolymj.2019.109300
|View full text |Cite
|
Sign up to set email alerts
|

A new ethanol biosensor based on polyfluorene-g-poly(ethylene glycol) and multiwalled carbon nanotubes

Abstract: Functionalization of the conjugated polymers has gained considerable interest in the biomedical engineering and biosensing applications as distinct properties can be imparted to the corresponding pristine analogues. In the present work, we report a novel sensing platform for the quantification of ethanol through a macromolecular design involving polyfluorene-g-poly(ethylene glycol) (PF-g-PEG) and multiwalled carbon nanotubes (MWCNTs). First, poly(ethylene glycol) with fluorene functionality (PEG-FL) was synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Because the CNTs have electrochemical stability and high surface area, they are very employed in sensors and biosensors. 15,16 Screen printed electrodes (SPEs) have also been widely employed in sensors for their especially low cost, fast response and large-scale production. 17 Regardless of these advantages, signal conductivity remains a weak point of SPE electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Because the CNTs have electrochemical stability and high surface area, they are very employed in sensors and biosensors. 15,16 Screen printed electrodes (SPEs) have also been widely employed in sensors for their especially low cost, fast response and large-scale production. 17 Regardless of these advantages, signal conductivity remains a weak point of SPE electrode.…”
Section: Introductionmentioning
confidence: 99%
“…The cathodic peak current showed a good linear response to the fraction of MDR with a correlation coefficient of 0.995 was observed for the cathodic peak current indicating an easy prediction of the MDR fraction based on the calibration curve of the cathodic peak current versus the fraction of MDR [ 72 ]. A sensor-based on polyfluorene-g-poly(ethylene glycol) (PF-g-PEG) and MWCNTs was developed for the quantification of ethanol in alcoholic drinks by Bekmezci et al, with high sensitivity [ 73 ]. Ghrera et al fabricated an impedimetric microfluidic-based biosensor for quantification of the DNA sequence specific to chronic myelogenous leukemia (CML).…”
Section: Biomedical Applications Of Carbon Nanotubesmentioning
confidence: 99%
“…There have been several studies on how enzyme‐incorporated nano‐biosensors have been found promising. For example, alcohol dehydrogenase/diamond NPs on phenothiazine support matrix (Revenga‐Parra et al, 2020), screen‐printed electrodes modified with GNPs and MWCNTs/polyneutral red film/alcohol dehydrogenase (Bilgi & Ayranci, 2016), polyfluorene‐g‐polyethylene glycol/MWCNTs/alcohol oxidase (Bekmezci et al, 2020) and the immobilization of alcohol dehydrogenase on Fe 3 O 4 @Au NPs (Samphao et al, 2015). Table 6 shows the summary of the enzyme‐incorporated biosensors using nanomaterials.…”
Section: Enzyme‐incorporated Nanomaterials In Various Applicationsmentioning
confidence: 99%